Hungarian Monitoring, 12 March 1990 . [Magyar rádiófigyelő], 1990. március 12 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Situation in Lithuania - Changes in Washington's Nicaragua policy - Gabčíkovo-Nagymaros dam - GDR state secretary's secret company - Soviet presidential system voted in Domestic Affairs: - Highest state awards ceremony on March 15 - Czech premier Pithart's visit - Soviet troop withdrawals - Interview with Árpád Göncz, president of the Writers' Association - Elections: József Antall's election portrait, press conferences, announcements, rallies, technical arrangements Economy: - Kuwaiti oil minister holds talks with Tamás Beck Külpolitika: - Litvániai helyzet - Változás Washington Nicaragua politikájában - A bősi vízlépcső - Az NDK-beli állampárt titkos vállalata - Megszavazták a szovjet elnöki rendszert Belpolitika: - A legmagasabb állami kitüntetések kiosztása márc. 15. alkalmából - Pithart cseh miniszterelnök látogatás - Szovjet csapatkivonás - Interjú Göncz Árpáddal, az Írószövetség elnökével - Választás: Antall József választási portréja, sajtótájékoztatók, nyilatkozatok, nagygyűlések, a technikai lebonyolítás kérdései Gazdaság: - Beck Tamással tárgyal a kuvaiti olaj miniszter